Morfogénesis de la fase sexual de Blechnum chilense y Blechnum cycadifolium (Pterophyta: Blechnaceae) - Pérez-García, Blanca; Mendoza, Aniceto; Ricci, Marcia (Revista de Biología Tropical, 1996)
The results of morphogenetic studies of the sexual phase of Blechnum chilense and B. cycadifolium are presented in this paper. In both species the spores are monolete, ellipsoidal, non-chIorophyllous, and the germination is of the Vittaria-type. The development pattern of the prothallia is of the Aspidium-type in B. cycadifolium for the unicellular, papilated and secretory trichomes, and the Adiantum-type in B. chilense, whose prothallia are naked. The adult gametophyte of B. cycadifolium is cordate-spatulate and with trichomes and in B. chilense, it is cordate-reniform and naked. The gametangia of B. chilense are of the common type of the leptosporangiate ferns. The first leaves appeared after 4'/2 months in B. chilense and in B. cycadifolium after 7 months of culture.